Trophic structure and fishing impacts on an oligotrophic ecosystem in the Western Mediterranean: the Balearic Islands - Paula Sánchez-Zulueta; María Valls; Beatriz Guijarro; María Ángeles Torres; María Ángeles Zapata; Marta Coll; Xavier Corrales; Eider Andonegi; Marta Díaz-Valdés; Enric Massutí; Francesc Ordines (Frontiers in Marine Science, 2023)
Within the context of the ecosystem approach to fisheries management, an ecosystem model was developed for the Balearic Islands in the early 2000s, covering from 0 to 800 m of depth. The aim of the study was to describe the structure and functioning of the ecosystem together with the fishing impacts. The results show that the biomass of the primary producers (PP), mainly dominated by Posidonia oceanica meadows and red algae beds, represented a high percentage of the biomass (39.20%) in the ecosystem. Most of the trophic flows occurred between PP (mostly benthic) and trophic level II. The mixed trophic impact analysis also highlighted a positive impact of the functional groups (FGs) at the base of the food web. Besides, there were important trophic flows between several demersal FGs, and many groups of the pelagic compartment, confirming the importance of the benthopelagic coupling previously reported. The mean trophic level of the catch (mTLc=2.76) was lower than those reported in adjacent areas due to the discard of benthic producers. By excluding benthic PP, the Balearic Islands showed the highest mTLc (3.44) among all the Mediterranean areas modelled, probably due to differences in the trophic structure, lower fisheries exploitation levels and lower development of the purse seine fleet targeting small pelagic fishes. The mean transfer efficiency (21.80%) was double than the global average (10%), which highlights the oligotrophy of the system, the importance of demersal production which has lower rates of transfer through the food web, and a more efficient use of nutrients in the ecosystem. Sponges, one of the most important groups of benthic invertebrates in the Balearic Archipelago, are known to recycle dissolved organic matter, which is reintroduced into the food web similar to the microbial loop, but the magnitude of this and other processes remains still unknown in this area. The present study is a first step to develop spatio-temporal simulations under different exploitation scenarios and to calculate ecological indicators to assess the state of the marine environment in this region.

Modelling land use planning: Socioecological integrated analysis of metropolitan green infrastructures - Joan Marull; Roc Padró; María José La Rota-Aguilera; Joan Pino; Annalisa Giocoli; Jacob Cirera; Núria Ruiz-Forés; Francesc Coll; Tarik Serrano-Tovar; Raúl Velasco-Fernández (Land Use Policy, 2023)

Correction to: The impacts of agricultural and urban land-use changes on plant and bird biodiversity in Costa Rica (1986–2014) - Andrea Montero; Joan Marull; Enric Tello; Claudio Cattaneo; Francesc Coll; Manel Pons; Juan Infante-Amate; Alexander Urrego-Mesa; Alfredo Fernández-Landa; Manuel Vargas (Regional Environmental Change, 2021)

The impacts of agricultural and urban land-use changes on plant and bird biodiversity in Costa Rica (1986–2014) - Andrea Montero; Joan Marull; Enric Tello; Claudio Cattaneo; Francesc Coll; Manel Pons; Juan Infante-Amate; Alexander Urrego-Mesa; Alfredo Fernández-Landa; Manuel Vargas (Regional Environmental Change, 2021)

Long-term bio-cultural heritage: exploring the intermediate disturbance hypothesis in agro-ecological landscapes (Mallorca, c. 1850–2012) - Joan Marull; Enric Tello; Nofre Fullana; Ivan Murray; Gabriel Jover; Carme Font; Francesc Coll; Elena Domene; Veronica Leoni; Trejsi Decolli (Biodiversity and Conservation, 2015)

Exploring the links between forest transition and landscape changes in the Mediterranean. Does forest recovery really lead to better landscape quality? - Joan Marull; Iago Otero; Constantí Stefanescu; Enric Tello; Marta Miralles; Francesc Coll; Manel Pons; Giovanna L. Diana (Agroforestry Systems, 2015)

Overlooked impacts and challenges of the new E uropean discard ban - Francesc Sardà; Marta Coll; Johanna J Heymans; Konstantinos I Stergiou (Fish and Fisheries, 2015)
Discards are the portion of animal and plant material in the catch that is dumped back at sea. The C ommon F isheries P olicy plan proposed by the E uropean C ommission for 2014–2020 presents a controversial goal: to enforce the landing of fishing discards as a measure to encourage their reduction. This historical and political decision will shape the future of the fishing exploitation in E uropean S eas. Discards generated by E uropean fleets are not negligible, and its reduction is an ecological, socioeconomical and moral imperative. However, it must be achieved through the reduction in discards at source and the promotion of selective and non‐destructive gears. We argue it is doubtful that this discard ban will result in an effective reduction of discards. The proposed measure may, in fact, negatively affect ecosystems at all levels of biological hierarchy by disregarding the E cosystem‐ B ased A pproach to F isheries and the P recautionary P rinciple. It could negatively impact several species by increasing fishing mortality, also commercial species if discards are not accounted in the total allowable catch. Communities preying on discards will likely be affected. The role discards currently play in the energy turnover of current ecosystems will be modified and should be fully evaluated. The landing of discards will likely generate new markets of fishmeal due to the growing demands for marine living resources. The ban will require substantial public investment to deal with technical problems on board and to control and enforce. Therefore, this measure should be only implemented after rigorous scientific and technical studies have been developed.